Diagnostic mistakes of culturally diverse individuals when using North American neuropsychological tests. Issue 1 (2nd January 2017) - Daugherty, Julia C.; Puente, Antonio E.; Fasfous, Ahmed F.; Hidalgo-Ruzzante, Natalia; Pérez-Garcia, Miguel
ABSTRACT: Although the role of culture has increasingly gained acceptance in clinical neuropsychology, relatively minimal research exists regarding the actual impact on clinical activities. In this study, we assess how using North American neuropsychological tests affects diagnostic accuracy in cognitive disorders of culturally diverse individuals. To address this question, participants from Colombia, Morocco, and Spain were administered five commonly used neuropsychological tests and the test results were used to determine whether they would be classified as having the DSM-5 diagnostic criteria for Mild Cognitive and Major Cognitive Disorder. Results reveal that diagnostic error occurred up to 20% of the time, and that the frequency of misdiagnosis differed by nationality. These results provide evidence that using tests from one culture to assess individuals from other cultures produces significant false positives. Findings are discussed in terms of the foundations of neuropsychological assessment and its relationship to cultural variables.